Diagnostic Yields of Trio-WES Accompanied by CNVseq for Rare Neurodevelopmental Disorders - Gao, Chao; Wang, Xiaona; Mei, Shiyue; Li, Dongxiao; Duan, Jiali; Zhang, Pei; Chen, Baiyun; Han, Liang; Gao, Yang; Yang, Zhenhua; Li, Bing; Yang, Xiu-An (Frontiers in Genetics, 2019)
Objective: This study is to investigate the diagnostic yield of the combination of trio whole exome sequencing (Trio-WES) and copy number variation sequencing (CNVseq) for rare neurodevelopmental disorders (NDDs). Methods: Clinical data from consecutive paediatric patients who were diagnosed with rare NDDs that were suspected to be monogenic disorders, who were admitted to our hospital from Apr 2017 to Mar 2019, and who underwent next generation sequencing (NGS) were extracted from the medical records. Patients for whom Trio-WES and CNVseq data were available were enrolled in this study. Sanger sequencing was applied for the validation of the variants identified by Trio-WES. Sequence alignment and structural modelling were conducted for analysing the possibility of the variants in the onset of the NDDs. Results: In total, 54 patients were enrolled in this study, with the median age of 15(8-26) months. A total of 242 phenotypic abnormalities belonging to 20 different systems were identified in the cohort. Twenty-four patients were diagnosed by Trio-WES, eight patients were diagnosed by CNVseq, and one case was identified by both WES and CNVseq. Compared with Trio-WES, the diagnosis rate of Trio-WES accompanied by CNVseq was significantly higher (P=0.016). Trio-WES identified 36 variants in 26 different genes, among which 27 variants were novel. CNVseq detected four duplications and eight deletions, ranging from 310 kb to 23.27 Mb. Our case examples demonstrated the high heterogeneity of NDDs and showed the challenges of rare NDDs for physicians. Conclusion: The significantly higher diagnosis rate of Trio-WES accompanied by CNVseq makes this strategy a potential alternative to the most widely used approaches for pediatric children with rare and undiagnosed NDDs.